Cidade como lugar de experiência: uma percepção pelas imagens dos fotógrafos Mariano Klautau Filho e Paula Sampaio - MOURA, Simone de Oliveira (Universidade Federal do Pará, 2017)
This research was developed to study the city's image produced by two contemporary photographers working in Belém and other cities, which are: Mariano Klautau Filho and Paula Sampaio. Based on the understanding of the city and image, with reference aisthesis concept proposed by James Hillman in the city feel from the expanded notion of psychic reality, anthropological approach discussed by Hans Belting image that distinguishes image and medium, and in dialogue with other authors, we sought to understand what image of the city is developed by photographers research subjects, taking into account the discourses, experiences and photographs of urban environment, outlining a perception of the image of the city. This study was done by means of the assessment, selection and analysis of the work of these photographers that emerged from the 1980s in the artistic context in Belém. The methodological approach used was qualitative and inductive analysis, using the method bibliographic, documentary and semi-structured interviews to survey and knowledge of photographic production of these authors, their discourses and experiences in Belém related to urban themes.